Hubungan antara Perceived Social Support dan Stres Akademik pada Mahasiswa Rantau Tingkat Akhir di Universitas Negeri Surabaya - Rabbani, Aqila Nadra; Oktaviana, Mimbar (Lembaga Teewan Journal Solutions, 2026)
This study analyzes the relationship between perceived social support and academic stress among out-of-town final-year students at Surabaya State University. A quantitative correlational approach with a cross-sectional design was used, involving 169 participants. Data were collected using the 12-item Multidimensional Perceived Social Support Scale (MSPSS) and the 19-item Educational Stress Scale for Adolescents (ESSA). Spearman correlation analysis was applied due to non-normal data distribution. Results showed a significant negative relationship between perceived social support and academic stress (ρ = -0.214, p = 0.005). Descriptive analysis indicated moderate-to-high perceived social support (M = 38.314, SD = 5.451) and moderate academic stress (M = 62.491, SD = 13.611). These findings suggest that higher social support from family, friends, and significant others is associated with lower academic stress. Despite the weak correlation strength, the significant p-value indicates a reliable relationship. Other factors such as self-confidence, resilience, and coping strategies may also contribute. A comprehensive intervention program combining social support enhancement with internal psychological resource strengthening is recommended to support students' academic well-being.